The Infallibility of the Prophet and Divine Admonition in Sūrah ʿAbasa (Verses 1–10): An Analysis from the Perspective of the Adhwāʾ al-Bayān Tafsīr - Umro Lania Hasibuan; Jani Arni; Lukmanul Hakim; Edi Hermanto; Muhammad Raffin Althafulayya (Al-Qudwah: Jurnal Studi Al-Qur'an dan Hadis, 2026)
The concept of the Prophet Muḥammad’s (peace be upon him) infallibility (ʿiṣmah) represents a fundamental doctrine within Islamic theology and has been the focus of extensive scholarly debate, particularly in relation to the Qur’ānic verses of ʿitāb (divine admonition), notably Sūrah ʿAbasa (1–10). Diverse interpretations of these verses have produced varying perspectives concerning the interplay between prophetic infallibility and Allah’s admonition in the Qur’ān. This study seeks to examine the notion of prophetic infallibility in Sūrah ʿAbasa (1–10) through the exegesis of Muḥammad al-Amīn al-Shinqīṭī as presented in Tafsīr Aḍwāʾ al-Bayān. Employing a library research methodology with a descriptive-analytical approach, the research utilises primary data from Tafsīr Aḍwāʾ al-Bayān alongside secondary sources encompassing works on Qur’ānic exegesis, ʿUlūm al-Qurʾān, and pertinent studies in Islamic theology. The findings reveal that al-Shinqīṭī interprets the admonition in Sūrah ʿAbasa not as indicative of the Prophet’s sin or error, but rather as a form of taʾdīb rabbānī (divine instruction) aimed at refining the Prophet’s method of daʿwah, without contravening the principle of prophetic infallibility. Furthermore, the admonition underscores the principle of human equality before divine revelation, emphasising that the orientation of daʿwah should be determined by receptivity to divine guidance (hidāyah) rather than social status. This study contributes to the field of theological Qur’ānic exegesis by demonstrating that al-Shinqīṭī’s interpretation offers a coherent synthesis between the doctrine of prophetic infallibility and the verses of ʿitāb, thereby providing a more nuanced understanding of the relationship between divine revelation, divine instruction, and prophetic authority.